PENERAPAN MODEL PEMBELAJARAN ACCELERATED LEARNING INCLUDE BY DISCOVERY (ALID) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS (KPS) DAN BERPIKIR ANALITIS PESERTA DIDIK KELAS X FARMASI SMK MUHAMMADIYAH 3 PURWOKERTO PADA MATERI JARINGAN HEWAN - Kuntari, Riskah Tiyan (Jurnal Analisis Pendidikan Sosial, 2024)
Learning Biology as the parts of science comprised by theories, principals, and science’s skills. The research was Classroom Action Research. The aims of this research were to improve science processing skills and analytical thinking for 10th grade of Farmacy Student at SMK Muhammadiyah 3 Purwokerto in the topic of Animal Tissue through learning model called Accelerated Include by Discovery (ALID). The research done in two cycles. For each cycle, there were planning, acting, observation, and reflecting stages. The learning material delivered in the first cycle was about Epithelial tissue and muscle tissues, the in the second cycle was about Nervous tissue and connective tissue on the vertebrate . The subject of the research was the students of grade 10 Farmacy at SMK Muhammadiyah 3 Purwokerto year 2019/2020 which has 28 students in the class. The objectives of the research focused on the analytical thinking and the science processing skills. The data collections were obtained through interview, observation, and evaluation test. The research instruments were test items, observational sheets, and observational guidelines. The data had been analysed through quantitative descriptive. Accelerated Include by Discovery (ALID) learning could improve the 10th grade of Farmacy students’ science processing skills and their analytical thinking ability. There was science processing skills’ improvement from cycle one to cycle two. In cycle 1, there are 20 students with the percentage 71,4 % got well criteria, and there were 25 students got the percentage 89,28 % of well criteria in the second cycle. In addition, the evaluation test of analytical thinking got class requirement score in the first cycle around 64,28 % with class’ average score 72,07, meanwhile in the second cycle, it improved 82,14 % for class requirement score with class’ average score 80,36.